2017
DOI: 10.1088/1741-4326/aa720c
|View full text |Cite
|
Sign up to set email alerts
|

Phase-space dependent critical gradient behavior of fast-ion transport due to Alfvén eigenmodes

Abstract: Experiments in the DIII-D tokamak show that many overlapping small-amplitude Alfvén eigenmodes (AEs) cause fast-ion transport to sharply increase above a critical threshold in beam power, leading to fast-ion density profile resilience and reduced fusion performance. The threshold is above the AE linear stability limit and varies between diagnostics that are sensitive to different parts of fast-ion phase-space. Comparison with theoretical analysis using the nova and orbit codes shows that, for the neutral parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 48 publications
7
34
0
Order By: Relevance
“…Other examples of a transport threshold will appear in a forthcoming publication. 7 Evidence that the transport threshold exceeds the linear stability threshold is also found in steady-state scenario plasmas. Figure 4 of Ref.…”
Section: Critical Gradient Behaviormentioning
confidence: 90%
See 2 more Smart Citations
“…Other examples of a transport threshold will appear in a forthcoming publication. 7 Evidence that the transport threshold exceeds the linear stability threshold is also found in steady-state scenario plasmas. Figure 4 of Ref.…”
Section: Critical Gradient Behaviormentioning
confidence: 90%
“…Details of the comparison between the measured threshold and stochasticity theory are the focus of a forthcoming paper. 7 Because different modes interact with fast ions in different parts of phase space, the measured threshold depends sensitively on both the diagnostic and on the fast-ion population that drives the modes. 7 Detailed probing of transport in phase space utilizes the combination of a modulated source and an array of fast-ion diagnostics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple unstable RSAEs and TAEs are excited using early deuterium beam power injected at 70-81 keV, with 4.0 MW of co-current, on-axis NBI, 0.7 MW of cocurrent, off-axis NBI, and 1.7 MW of counter-current, on-axis NBI. This discharge has excellent diagnostic coverage and was examined extensively in studies [3,4,15] of AE-induced fast-ion transport in critical gradient experiments. Figure 1(a) shows the spectrogram of electron cyclotron emission (ECE) data during the current ramp for shot #159243, along with calculated RSAE frequency evolution from an ad hoc model [16].…”
Section: Diii-d Ep Experiments For Verification and Validationmentioning
confidence: 99%
“…Furthermore, experiments and simulations in the literature 2,15,22,23 have shown that rapid long range frequency chirping across a wide range of frequency chirps (mode 'avalanching') is correlated with high amounts of fast ion loss. Other work has shown that mode-mode destabilisation may play a role in Alfvénic frequency chirping -activity in the KTF frequency range (∼ 1 kHz to 30 kHz) may instigate Alfvénic activity, and vice-versa.…”
Section: Fast Ion Lossmentioning
confidence: 99%